Emotions Et Sentiments Induits Par Les Evaluations Sommatives Chez Des Apprenants En Situation De Formation Professionnelle - Mathias Kyelem; Amadou Tamboura; Daniel Favre (International Journal of Evaluation and Research in Education (IJERE), 2015)
To prove the quality of their teaching activities, school leaders and teachers are almost always resort to summative assessments; the level of the scores obtained by the largest number of students for assays or exams is the best indicator of the quality of learning achieved by students. Summative assessments become sufficiently numerous to help establish report cards and rankings monthly to the detriment of a formative assessment needed to regulate and guide the educational activity. All this does not take into account the dynamics of the error in learning and the stress state in which the learner is then subjected to a strong emotional pressure. Research in neuroscience show that a high level of anxiety causes a deficit in the ability to perform tasks involving solving non-routine problems. In this study, most of the respondents have had several years of professional training and a long teaching practice. It was interesting to explore their relationship to error and their level of apprehension of the summative evaluation in a context where they are in the process of "exercise" the student work. In general, the results show that the dominant fundamental emotion among all respondents is the fear as with most recurrent words anxiety, worry, fear, feelings or emotions that inhibit the action.